Technical and financial aspects of albino full red guppy fish cultivation business (Poecilia reticulata) - Wahyu, Wahyu; Utami, Diah Ayu Satyari; Adrianti, Ni Putu Vika (Universitas Malikussaleh, 2025)
Guppy fish (Poecilia reticulata) albino full red variant is favored by freshwater ornamental fish hobbyists and has high demand. This study analyzes the technical and financial aspects of the guppy fish production business at Swasti Farm, Sleman, Yogyakarta. The study was conducted using a case study method. Analysis was conducted descriptively for data obtained through direct observation, interviews, and literature studies. The production activities of albino full red (AFR) guppy fish at Swasti Farm consist of; selection and maintenance of broodstock; fish spawning; fry rearing and nursery; and harvesting. Water quality management and fish health management also proceed during the production cycle. The guppy broodstock used is 3-4 months old from Swasti Farm. Fish spawning is conducted with a ratio of 2:1 between male and female broodstock. The number of offspring produced in one spawning period by the female broodstock is 42, and the final survival rate during the 80-day nursery period is 63%. The cultivation technique by Swasti Farm has been carried out well. The business profit achieved is Rp. 13,422,333 with an R/C ratio of 1.3 and a payback period (PP) of 1.3 years. The business analysis shows that the production of albino full red (AFR) guppy is a profitable and feasible business to operate. However, it is necessary to optimize the performance of cultivation production and increase the number of production units to increase profits and ensure business sustainability. Keywords: Albino Full Red; Financial Aspect; Guppy; Technical Aspec